IMPLEMENTATION OF THE AL-JAWARIH METHOD IN INSTILLING RELIGIOUS CHARACTER OF CHILDREN AGED 5-6 YEARS AT MADRASAH RAUDHATUL ATHFAL (RA) ALAM YA BUNAYYA BUNGO - Nia Putri Agustina; Muhammad Sholihin; Wiwin Narti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to describe the implementation of the Al-Jawarih method in instilling the religious character of children aged 5–6 years in Madrasah Raudhatul Athfal Alam Ya Bunayya Bungo. The Al-Jawarih method is a learning approach that emphasizes understanding the Qur'an not only as reading, but as a guide to life that is practiced through the involvement of all limbs (jawarih). This study uses a descriptive qualitative approach. Data collection techniques are carried out through observation, interviews, and field notes. The results of the study show that the implementation of the Al-Jawarih method is carried out through four main components, namely habituation of routine activities, habituation of spontaneous activities, programmatic activities, and teacher examples. The process of instilling religious values takes place through the stages of knowing, feeling, understanding, and gratitude, which is then manifested in daily behavior. Learning activities are associated with children's direct experiences, such as outing activities (tadabur alam), MABIT (night of faith and piety) and green labs, so that children are able to connect verses of the Qur'an with the reality of life. The findings of the study show that there is a change in children's behavior that is more polite, honest, and caring, an increase in religious habits such as praying, saying greetings, and reading the Qur'an, as well as developing independence in carrying out simple worship. In addition, the role of teachers as role models and support for the school and family environment is an important factor in the success of cultivating religious character. Thus, the Al-Jawarih method has proven effective in instilling the religious character of early childhood holistically through the integration of learning, habituation, and hands-on experience.